Marketing in and for a sustainable society - Malhotra, Naresh K. (Review of marketing research,, 2016)
This special issue will assemble a set of current, comprehensive/extended review articles/chapters written by distinguished experts on the state-of-the-art of marketing research and future prospects in the transition towards sustainable society. Reviews have been written for impact on marketing thought and clearly articulate the significance, and present critical perspectives and integrated theories on marketing for sustainability. This special issue features contributions from several top scholars including former editors of top journals in marketing.